Urbanization Leads to Increases in pH, Carbonate, and Soil Organic Matter Stocks of Arable Soils of Kumasi, Ghana (West Africa) - Asabere, Stephen Boahen; Zeppenfeld, Thorsten; Nketia, Kwabena Abrefa; Sauer, Daniela (Frontiers in Environmental Science, 2018)
Tropical soils typically have low cation exchange capacity and nutrient contents. Both are enhanced by soil organic matter (SOM), which is thus particularly important for the fertility of these soils. In this study, we assessed the influence of urbanization on SOM, carbonate contents and pH of arable soils of Kumasi (Ghana, West Africa), since rapid urban sprawl is widespread in West Africa, whereby in many West African cities urban farming is pivotal to the food security of their population. Based on satellite imagery for the year 1986, we distinguished long-term and short-term urban arable soils, whereby long-term urban soils were urban already in 1986 (thus  30 years, as soil sampling took place in 2016), and short-term urban soils became urban afterwards (< 30 years). We took 618 undisturbed topsoil samples (0-10 cm) from 206 urban arable fields. The factors land-use (maize fields) and soil (Ferric Acrisols) were kept largely constant. The fine-earth was analysed for pH (water), carbonate contents, loss on ignition (LOI), total C (TC) and N (TN). SOM contents were obtained from LOI (SOMLOI). All element contents were transformed to bulk soil element stocks per m2. Differences between short-term and long-term urban soils were identified by a set of linear mixed models. Coarse fragments were more abundant in the long-term (16%) compared to the short-term (10%) urban soils, because of solid municipal waste that accumulates over time in urban soils. TC and SOMLOI concentrations of the fine earth, pH and C/N ratios were all significantly higher in the long-term urban soils. SOC concentrations in the fine earth, as well as bulk soil stocks of TC, SOC and SOMLOI were also higher in the long-term urban soils, but at a lower degree of confidence, due to variable bulk densities and contents of coarse fragments. We conclude that dumping of organic and inorganic waste (including ash, bones, egg shells, concrete and mortar) increases SOM stocks and soil pH, but also leads to accumulation of non-degradable solid materials (including plastic, metals etc.). These findings point to the need of an improved urban waste management system, separating degradable and non-degradable waste.